Die in Jugoslawien lebende ungarische Minderheit in der ungarischen Aussenpolitik zwischen den beiden Weltkriegen (1919-1938) - Hornyák, Árpád (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
In the 1920019s and 1930â019s Hungarian minority played a role of secondary importance in Hungarian foreign policy conducted towards Yugoslavia. It was primarily the instrument of Hungarian foreign policy in order to reach its main goal to disintegrate the Little Entente. By requests of giving concessions to Hungarian minority in Yugoslavia the Hungarian government wanted to demonstrate its approach to Belgrade and this way to ameliorate circumstances for Hungarian foreign policy. On the other hand the Hungarian minority for Yugoslavian foreign policy was an instrument too. Their treatment has changed according the importance that Belgrade gave to friendship of Hungary.
Keywords: Jugoslavija; Yugoslavia; narodne manjšine; madžarska manjšina; Hungary; Madžarska; zunanja politika